(untitled) (ShodhVarta, 2025)
Man is a social animal and he uses various mediums to express his feelings and thoughts. These mediums include genres like poetry, story, essay, report, diary, etc. ‘School diary’ is a technique that plays an important role in the academic and personal development of students. This technique is also used by schools to develop students’ activity management and organizational skills. ‘School diary’ helps in maintaining records of the teachings, planning schedules, and marking students’ progress, which helps students develop a sense of responsibility and time management. The Daily use of a ‘School diary’ also develops a sense of encouragement among students to participate actively in discipline, academic, and extracurricular activities. Will the use of school diaries be mandatory for all schools and all students at present? In The present research article researcher has observed the school diary of a class I student studying in a private school in the Jaunpur district of Uttar Pradesh (Academy, M). Thereafter, through the presented research study, the researcher has tried to explain the rationale of the school diary as well as highlight the benefits of the school diary.